New contributions to the computerized management of oil spills: its application to "refuge areas" - Bergueiro, JR; Moreno, S; Hernández, L; Cavilla, JM; Gómez, JJ; González, J (Nexo Revista Científica, 2011)
The purpose of this paper is to describe most of the procedures to follow in deciding whether you should transfer a tanker wrecked in a "refuge zone". In reaching this decision, it should consider different procedures, in order to objectify the best decision. It is important to know very well the features and infrastructures of the different coastal areas, which can be considered as possible "refuge zones". Based on the foregoing analysis, it has developed a program consisting of several modules to permit compute data of great importance, among which include matrices of environmental and infrastructural values that allow for the calculation of certain factors for transfer actions and preparation of the tanker (transfer time of the tanker, berthing time and connection time to the pumping systems, time of emptying the oil in storage tanks, transfer to another tanker, etc). In addition, this program allows us to estimate the costs of cleaning and restoration, as well as losses in the tourism sector. Keywords: Hydrocarbons; Place of refuge; Oil spills DOI: http://dx.doi.org/10.5377/nexo.v24i1.590 Nexo, Vol. 24, No. 1, pp. 11-19, 2011